Retroperitoneal drainage versus no drainage after pelvic lymphadenectomy for the prevention of lymphocyst formation in women with gynaecological malignancies - Kittipat Charoenkwan (2018)
© 2017 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. Background: This is an updated version of an original Cochrane review published in Issue 6, 2014. Pelvic lymphadenectomy is associated with significant complications including lymphocyst formation and related morbidities. Retroperitoneal drainage using suction drains has been recommended as a method to prevent such complications. However, findings from recent studies have challenged this policy. Objectives: To assess the effects of retroperitoneal drainage versus no drainage after pelvic lymphadenectomy on lymphocyst formation and related morbidities in women with gynaecological cancer. Search methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL, Issue 3, 2017) in the Cochrane Library, electronic databases MEDLINE (1946 to March Week 2, 2017), Embase (1980 to 2017 week 12), and the citation lists of relevant publications. We also searched the trial registries for ongoing trials on 20 May 2017. Selection criteria: Randomised controlled trials (RCTs) that compared the effect of retroperitoneal drainage versus no drainage after pelvic lymphadenectomy in women with gynaecological cancer. Retroperitoneal drainage was defined as placement of passive or active suction drains in pelvic retroperitoneal spaces. No drainage was defined as no placement of passive or active suction drains in pelvic retroperitoneal spaces. Data collection and analysis: We assessed studies using methodological quality criteria. For dichotomous data, we calculated risk ratios (RRs) and 95% confidence intervals (CIs). We examined continuous data using mean difference (MD) and 95% CI. Main results: Since the last version of this review, we have identified no new studies for inclusion. The review included four studies with 571 women. Regarding short-term outcomes (within four weeks after surgery), retroperitoneal drainage was associated with a comparable rate of overall lymphocyst formation when all methods of pelvic peritoneum management were considered together (2 studies; 204 women; RR 0.76, 95% CI 0.04 to 13.35; moderate-quality evidence). When the pelvic peritoneum was left open, the rates of overall lymphocyst formation (1 study; 110 women; RR 2.29, 95% CI 1.38 to 3.79) and symptomatic lymphocyst formation (2 studies; 237 women; RR 3.25, 95% CI 1.26 to 8.37) were higher in the drained group. At 12 months after surgery, the rates of overall lymphocyst formation were comparable between the groups (1 study; 232 women; RR 1.48, 95% CI 0.89 to 2.45; high-quality evidence). However, there was a trend toward increased risk of symptomatic lymphocyst formation in the group with drains (1 study; 232 women; RR 7.12, 95% CI 0.89 to 56.97; low-quality evidence). Authors' conclusions: Placement of retroperitoneal tube drains has no benefit in the prevention of lymphocyst formation after pelvic lymphadenectomy in women with gynaecological malignancies. When the pelvic peritoneum is left open, the tube drain placement is associated with a higher risk of short- and long-term symptomatic lymphocyst formation. We found the quality of evidence using the GRADE approach to be moderate to high for most outcomes, except for symptomatic lymphocyst formation at 12 months after surgery, and unclear or low risk of bias.